Denoising diffusion‐weighted magnitude MR images using rank and edge constraints. Issue 3 (8th April 2013) - Lam, Fan; Babacan, S. Derin; Haldar, Justin P.; Weiner, Michael W.; Schuff, Norbert; Liang, Zhi‐Pei
<x xml:space="preserve">Abstract</x> Purpose To improve signal‐to‐noise ratio for diffusion‐weighted magnetic resonance images. Methods A new method is proposed for denoising diffusion‐weighted magnitude images. The proposed method formulates the denoising problem as an maximum a posteriori